2020
DOI: 10.5194/acp-20-9821-2020
|View full text |Cite
|
Sign up to set email alerts
|

Probing key organic substances driving new particle growth initiated by iodine nucleation in coastal atmosphere

Abstract: Abstract. Unlike the deep understanding of highly oxygenated organic molecules (HOMs) driving continental new particle formation (NPF), little is known about the organic compounds involved in coastal and open-ocean NPF. On the coastline of China we observed intense coastal NPF events initiated by iodine nucleation, but particle growth to cloud condensation nuclei (CCN) sizes was dominated by organic compounds. This article reveals a new group of C18,30HhOoNn and C20,24,28,33HhOo compounds with specific double-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 90 publications
2
2
0
Order By: Relevance
“…The concentrations of ∑ 19 iodoresorcinols and ∑ 18 iodonaphthols are 110 pg m –3 (range: 27.2–380 pg m –3 ) and 130 pg m –3 (range: 16.4–390 pg m –3 ), respectively, in the heating season, with the dominant species being 4-iodoresorcinol (median: 31.4 pg m –3 , range: 7.0–110 pg m –3 ) and 1-iodo-2-naphthol (median: 21.0 pg m –3 , range: 2.9–80.5 pg m –3 ). Although the total concentration of water-soluble OICs has been previously measured in marine aerosols, ,,, only a few studies reported the speciated concentration of OICs. , Our results are comparable to the other particle-phase organohalogen measurements during haze periods of heating season in Beijing. The concentrations of ∑ 37 OICs are at a similar level to the total concentration of 19 chlorinated polycyclic aromatic hydrocarbons (Cl-PAHs) and ∼10 times higher than that of 18 brominated PAHs, which indicate a high load of organohalogens in PM 2.5 of Beijing.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The concentrations of ∑ 19 iodoresorcinols and ∑ 18 iodonaphthols are 110 pg m –3 (range: 27.2–380 pg m –3 ) and 130 pg m –3 (range: 16.4–390 pg m –3 ), respectively, in the heating season, with the dominant species being 4-iodoresorcinol (median: 31.4 pg m –3 , range: 7.0–110 pg m –3 ) and 1-iodo-2-naphthol (median: 21.0 pg m –3 , range: 2.9–80.5 pg m –3 ). Although the total concentration of water-soluble OICs has been previously measured in marine aerosols, ,,, only a few studies reported the speciated concentration of OICs. , Our results are comparable to the other particle-phase organohalogen measurements during haze periods of heating season in Beijing. The concentrations of ∑ 37 OICs are at a similar level to the total concentration of 19 chlorinated polycyclic aromatic hydrocarbons (Cl-PAHs) and ∼10 times higher than that of 18 brominated PAHs, which indicate a high load of organohalogens in PM 2.5 of Beijing.…”
Section: Resultssupporting
confidence: 80%
“…Although the total concentration of watersoluble OICs has been previously measured in marine aerosols, 8,9,27,28 only a few studies reported the speciated concentration of OICs. 10,29 Our results are comparable to the other particle-phase organohalogen measurements during haze periods of heating season in Beijing. The concentrations of ∑ 37 OICs are at a similar level to the total concentration of 19 chlorinated polycyclic aromatic hydrocarbons (Cl-PAHs) and ∼10 times higher than that of 18 brominated PAHs, 30 which indicate a high load of organohalogens in PM 2.5 of Beijing.…”
Section: ■ Materials and Methodssupporting
confidence: 86%
“…A negative lag time, which means that particle components are being driven by nucleation rates, reflects the fact that particles need to grow to larger diameters to be detected by the c-ToF-AMS, whose detection efficiency is rather poor below 50 nm (see Section 2.5). Contrarily to previous studies at higher latitudes (Allan et al, 2015;Baccarini et al, 2020;Mäkelä et al, 2002;McFiggans et al, 2010;Wan et al, 2020;Yu et al, 2019), a clear link between iodine species and NPF events was not observed during the AEROCLO-sA campaign (example correlation with the I + fragment measured by the c-ToF-AMS shown in Table S4 in Supporting Information S1). However, NPF event of the 9 September (Figure 3a) occurs hours after a spike of the iodide ion, locally produced in the morning (Figure 3f), which may be driving nucleation even if it is only a minor contributor to aerosol mass at the size range detectable by the c-ToF-AMS.…”
Section: Resultsmentioning
confidence: 62%
“…For example, recent modelling work suggested that MSA could stabilise iodic acid, leading to higher particle formation rates when both MSA and iodic acid are present (Ning et al, 2022), but this has not yet been reported in measurements. Fieldwork in coastal China has shown that nucleation can involve both iodine and organic species (Wan et al, 2020), further highlighting the need to understand the interactions between different chemical species.…”
Section: Introductionmentioning
confidence: 99%